INTRAVITREAL NESVACUMAB (ANTIANGIOPOIETIN 2) PLUS AFLIBERCEPT IN DIABETIC MACULAR EDEMA: Phase 2 RUBY Randomized Trial. Issue 6 (22nd June 2022) - Brown, David M.; Boyer, David S.; Csaky, Karl; Vitti, Robert; Perlee, Lorah; Chu, Karen W.; Asmus, Friedrich; Leal, Sergio; Zeitz, Oliver; Cheng, Yenchieh; Schmelter, Thomas; Heier, Jeffrey S.
Abstract : Supplemental Digital Content is Available in the Text. In a Phase 2 study of patients with diabetic macular edema, combination treatment with intravitreal nesvacumab (antiangiopoietin 2) plus aflibercept (antivascular endothelial growth factor) demonstrated some evidence of anatomic improvements but did not demonstrate superior visual acuity benefits over intravitreal aflibercept alone. Abstract : Purpose: The purpose of this study was to compare intravitreal nesvacumab (anti-angiopoietin 2) plus aflibercept with intravitreal aflibercept injection (IAI) in diabetic macular edema. Methods: The eyes (n = 302) were randomized (1:2:3) to nesvacumab 3 mg + aflibercept 2 mg (LD combo), nesvacumab 6 mg + aflibercept 2 mg (HD combo), or IAI 2 mg at baseline, Weeks 4 and 8. LD combo continued every 8 weeks (q8w). HD combo was rerandomized at Week 12 to q8w or every 12 weeks (q12w); IAI to q8w, q12w, or HD combo q8w through Week 32. Results: Week 12 best-corrected visual acuity gains for LD and HD combo versus IAI were 6.8, 8.5, and 8.8 letters; Week 36 changes were similar. Central subfield retinal thickness reductions at Week 12 were −169.4, −184.0, and −174.6 µ m (nominal P = 0.0183, HD combo vs. IAI); Week 36 reductions for LD combo and HD combo q8w and q12w versus IAI were −210.4, −223.4, and −193.7 versus −61.9 µ m (nominal P < 0.05). At Week 12, 13.3% and 21.3% versus 15.2% had ≥2-step Diabetic Retinopathy Severity Scale improvement (LD and HD combos vs. IAI) and 59.6% and 66.3% versus 53.7% had complete foveal center fluid resolution. Safety was comparable across groups. Conclusion: Nesvacumab + aflibercept demonstrated no additional visual benefit over IAI. Anatomic improvements with HD combo may warrant further investigation.